Deletion of the lipid droplet protein kinase gene affects lipid droplets biogenesis, parasite infectivity, and resistance to trivalent antimony in Leishmania infantum. - Juliana Martins Ribeiro; Paula Alves Silva; Héllida Marina Costa-Silva; Ana Maria Murta Santi; Silvane Maria Fonseca Murta (Public Library of Science (PLoS), 2024)
The Lipid Droplet Protein Kinase (LDK) facilitates lipid droplet (LD) biogenesis, organelles involved in various metabolic and signaling functions in trypanosomatids. As LDK's function has not been previously explored in Leishmania spp., we utilized CRISPR/Cas9 technology to generate LDK-knockout lines of Leishmania infantum to investigate its role in this parasite. Our findings demonstrate that LDK is not an essential gene for L. infantum, as its deletion did not impede parasite survival. Furthermore, removing LDK did not impact the growth of promastigote forms of L. infantum lacking LDK. However, a noticeable reduction in LDs occurred during the stationary phase of parasite growth following LDK deletion. In the presence of myriocin, a LD inducer, LDK-knockout parasites displayed reduced LD abundance during both logarithmic and stationary growth phases compared to control parasites. Moreover, an infection analysis involving THP-1 cells revealed that 72 h post-infection, LDK-knockout L. infantum lines exhibited fewer infected macrophages and intracellular amastigotes than control parasites. LDK-knockout L. infantum lines also displayed 1.7 to 1.8 -fold greater resistance to trivalent antimony than control parasites. There were no observed alterations in susceptibility to amphotericin B, miltefosine, or menadione in LDK-knockout L. infantum lines. Our results suggest that LDK plays a crucial role in the biogenesis and/or maintenance of LDs in L. infantum, as well as in parasite infectivity and resistance to trivalent antimony.